Understanding the properties of fat, oil, and grease and their removal using grease interceptors. (15th October 2022) - Sultana, Nilufa; Roddick, Felicity; Gao, Li; Guo, Mike; Pramanik, Biplob Kumar
Highlights: Hydrolysis and saponification are the main mechanisms of FOG deposition in sewers. FOG characteristics vary markedly between dishwasher and handwash sink effluents. About 40–50% of FOG particles are less than 45 µm diameter. Conventional GIs are ineffective for removal of all FOG particles. Pre-treatment can improve the performance of GI system for FOG removal. Abstract: Treatment of wastewater with high levels of fat, oil, and grease (FOG), produced by the growing number (annually 2%) of food service establishments (FSEs), is a major concern for water utilities. About 30–40% of sewer blockages are caused primarily by the formation of FOG deposits in sewer pipes, and an annual additional maintenance cost is required for sewer management. To manage FOG deposition, FSEs are required to recover the FOG at the point of generation by installing grease interceptors (GIs) before release to the sewer system. The successful control of FOG deposition is largely dependent on clear understanding of its complex properties, pre-treatment processes, deposition mechanism and public awareness. The objective of this study is to provide a comprehensive understanding of the physicochemical properties of FOG, including particle size distribution and their removal efficiencies by existing GIs. Nowadays, generation of FOG particles of ≤45 µm is increasing because of the increasing use of automatic dishwashers. Current hybrid processes which comprise pre-treatment prior to GI use are ineffective since they are unable to completely remove particle sizes of ≤45 µm. Hence, there is potential for these particles to be released into the sewer system and eventually cause blockages. This critical review discusses the characteristics of effluents, including the particle size distributions generated from automatic dishwashers and handwash sinks. It concludes by providing some case studies and a perspective of the future opportunities to develop a novel GI process integrated with pre-treatment to remove particles of all sizes, including colloidal particles. Graphical abstract: Image, graphical abstract